2016
DOI: 10.1161/atvbaha.116.307586
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency Accelerates Coronary Artery Disease Progression in Swine

Abstract: Objective-The role of vitamin D deficiency in coronary artery disease (CAD) progression is uncertain. Chronic inflammation in epicardial adipose tissue (EAT) has been implicated in the pathogenesis of CAD. However, the molecular mechanism underlying vitamin D deficiency-enhanced inflammation in the EAT of diseased coronary arteries remains unknown. We examined a mechanistic link between 1,25-dihydroxyvitamin D-mediated suppression of nuclear factor-κB (NF-κB) transporter, karyopherin α4 (KPNA4) expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 43 publications
(44 reference statements)
1
54
0
3
Order By: Relevance
“…Low levels of vitamin D have been associated with increased risk of CVD such as coronary artery disease (CAD) [5], myocardial infarction (MI) [67], hypertrophy [8], cardiomyopathy [9–10], fibrosis [1112], heart failure (HF) [1314]. In addition, deficiency of vitamin D has been found in arterial diseases, including aneurysm [1516], peripheral arterial disease (PAD) [1719], arterial calcification [20], hypertension (HTN) [2122] and atherosclerosis [23] (Figures 2 and 3).…”
Section: Introductionmentioning
confidence: 99%
“…Low levels of vitamin D have been associated with increased risk of CVD such as coronary artery disease (CAD) [5], myocardial infarction (MI) [67], hypertrophy [8], cardiomyopathy [9–10], fibrosis [1112], heart failure (HF) [1314]. In addition, deficiency of vitamin D has been found in arterial diseases, including aneurysm [1516], peripheral arterial disease (PAD) [1719], arterial calcification [20], hypertension (HTN) [2122] and atherosclerosis [23] (Figures 2 and 3).…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian KPNA4 plays a role in regulating the nuclear transportation of type I IFN transcription factors, thereby triggering the expression of type I IFN and the subsequent immune response against virus infection (Zhu et al, 2015;Chen et al, 2016;Li et al, 2018). However, the role of avian KPNA4 in type I IFN expression was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Among the identified KPNAs, KPNA4 in the α3 subfamily is involved in the innate immune response against viral infection Ye et al, 2017). Several KPNA4 orthologues from different species including humans (Köhler et al, 1997), mice (Mihalas et al, 2015), pigs (Chen et al, 2016) and chickens (Caldwell et al, 2005) have been identified. In mammals, human KPNA4, a specific adaptor molecule, mediates the nuclear import of interferon (IFN) transcriptional regulators, such as NF-κB p50/p65 heterodimers and IFN regulatory factor (IRF) 3, thereby regulating type I IFN-mediated immune responses (Canton et al, 2018;Shaw et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…TNFα, IL-6, MCP-1 and pentraxin 3) in epicardial adipose tissue biopsy samples from human patients with coronary artery disease (24). Mechanistically, vitamin D controls inflammatory signaling pathways through regulation of key molecules including importin-α3 (karyopherin-α4), NF-κβ, and suppressor of cytokine signaling 3 (SOCS3) (9, 25, 26). …”
Section: Discussionmentioning
confidence: 99%